2018
DOI: 10.18203/2320-1770.ijrcog20182370
|View full text |Cite
|
Sign up to set email alerts
|

Risk of malignancy index 4 in preoperative evaluation of patients with ovarian tumours

Abstract: Background: Ovarian tumors usually presents as adnexal masses which may be benign or malignant. Accurate and timely diagnosis of an adnexal mass is a challenge for the gynecologists. Currently clinical examination, ultrasonographic assessment and ovarian tumour markers (CA 125, beta hCG, AFP, LDH) are routinely done at our centre to evaluate patients with ovarian tumours. The study was designed to evaluate the ability of RMI 4 to discriminate benign ovarian tumor from malignant ovarian tumor in patients attend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 12 publications
2
6
1
Order By: Relevance
“…The receiver operating curve for USG score in our study was 0.93. [20] Our results were similar to B.R Obeidat et al i.e area under curve 0.73. [18] Evaluation of Logistic regression analysis with histopathological diagnosis as a constant value, the only parameter i.e USG score can individually diagnose and differentiate benign from malignant adnexal masses (p value -0.0001).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The receiver operating curve for USG score in our study was 0.93. [20] Our results were similar to B.R Obeidat et al i.e area under curve 0.73. [18] Evaluation of Logistic regression analysis with histopathological diagnosis as a constant value, the only parameter i.e USG score can individually diagnose and differentiate benign from malignant adnexal masses (p value -0.0001).…”
Section: Discussionsupporting
confidence: 92%
“…[19] Recent study by 2018 Singhal S et al gave a sensitivity of 75% and specificity of 90% for CA-125 levels >35U/ml. [20] The best cut off value of CA-125 was 50 U/ml with a sensitivity of 87.3% and specificity of 93.5% in our study. [3] Analysis of 132 patients with ultrasound features in respect of benign and malignant patients are as follows.…”
Section: Discussionsupporting
confidence: 47%
“…15 Recent study by 2018 Singhal S et al gave a sensitivity of 75% and specificity of 90% for CA-125 levels > 35U/ml. 19 In our study, CA125 levels ≥ 35 U/ml had a sensitivity of 75.6%, the specificity of only 48.2%, PPV 43.6% and NPV of 78.8%. A higher prevalence of pelvic inflammatory diseases and endometriosis might have contributed to elevated CA125 levels in the majority of our patients along with fluctuation of CA125 during the menstrual cycles in premenopausal patients with adnexal masses and its more specificity for non-mucinous epithelial ovarian tumor might be the reason for its low diagnostic performance in the detection of malignant ovarian disease.…”
Section: Discussioncontrasting
confidence: 43%
“…Simsek et al reported a sensitivity of 78.6% and specificity of 63.5% for CA 125 at a cutoff value of 35 u/ml [ 10 ]. In a recent study, Singhal et al found a sensitivity of 75% and specificity of 90% for CA 125 levels > 35 u/ml [ 13 ]. Meanwhile, in this study, three out of 136 patients were malignant with CA 125 < 35 u/ml and 28 out of 55 were malignant with CA 125 > 35 u/ml (Table 2 ).…”
Section: Discussionmentioning
confidence: 99%